Clinical use and outcome of extracorporeal membrane oxygenation in patients with pulmonary embolism. (January 2022) - Hobohm, Lukas; Sagoschen, Ingo; Habertheuer, Andreas; Barco, Stefano; Valerio, Luca; Wild, Johannes; Schmidt, Frank P.; Gori, Tommaso; Münzel, Thomas; Konstantinides, Stavros; Keller, Karsten
Abstract: Aim of the study: Extracorporeal membrane oxygenation (ECMO) is considered a life-saving treatment option for patients in cardiogenic shock or cardiac arrest undergoing cardiopulmonary resuscitation (CPR) due to acute pulmonary embolism (PE). We sought to analyze use and outcome of ECMO with or without adjunctive treatment strategies in patients with acute PE. Methods: We retrospectively analyzed data on patient characteristics, treatments, and in-hospital outcomes for all PE patients (ICD-code I26) undergoing ECMO in Germany between 2005 and 2018. Results: At total of 1, 172, 354 patients were hospitalized with PE; of those, 2, 197 (0.2%) were treated with ECMO support. Cardiac arrest requiring cardiopulmonary resuscitation was present in 77, 196 (6.5%) patients. While more than one fourth of those patients were treated with systemic thrombolysis alone (n = 20, 839 patients; 27.0%), a minority of patients received thrombolysis and VA-ECMO (n = 165; 0.2%), embolectomy and VA-ECMO (n = 385; 0.5%) or VA-ECMOalone (n = 588; 0.8%). A multivariable logistic regression analysis indicated the lowest risk for in-hospital death in patients who received embolectomy in combination with VA-ECMO (OR, 0.50 [95% CI, 0.41–0.61], p < 0.001), thrombolysis and VA-ECMO (0.60 [0.43–0.85], p = 0.003) or VA-ECMO alone (0.68 [0.57–0.82], p < 0.001) compared to thrombolysis alone (1.04 [0.99–1.01], p = 0.116). Conclusion: Our findings suggest that the use of VA-ECMO alone or as part of a multi-pronged reperfusion approach including embolectomy or thrombolysis might offer survival advantages compared to thrombolysis alone in patients with PE deteriorating to cardiac arrest.